Fully Automated Radioligand Binding Filtration Assay for Membrane-Bound Receptors - A. Shrikhande; C. Courtney; D. Smith; M. Melch; M. McConkey; J. Bergeron; Stephen K-F. Wong (BioTechniques)
Here we describe a fully automated, hands-free radioligand filtration binding assay for dopamine D3 receptors. Three separate instruments were linked in tandem to perform the following operations: The Genmate and Genesis were linked to perform liquid handling, incubation, and the scheduling operations, while an automated harvester was used to perform rapid filtration. To minimize carryover of compounds, disposable tips were used for diluting and dispensing the compounds. A custom-designed tip holder was used to handle loading and pipetting by the Genmate 96-well pipettor. The assay for 84 compounds with six concentrations that spans six logs can be completed within 4 h. The reproducibility of the individual data point (cv < 10% between duplicates) and Ki (cv < 20%) is superior to that determined by manual procedures. Ki values of various dopamine ligands determined by the hands-free procedure are similar to published values. This technology reduces hands-on time (at least 70%), minimizes exposure to radioligands (up to 95%), and improves the reproducibility of results. The technology is applicable for high-throughput screening and rapid determination of structure-activity relationship of compounds for many other membrane-bound receptors.